MTHFR Gene C677T Polymorphism in Autism Spectrum Disorders - Sener, Elif Funda (Genet Res Int, 2014)
Aim. Autism is a subgroup of autism spectrum disorders, classified as a heterogeneous neurodevelopmental disorder and symptoms occur in the first three years of life. The etiology of autism is largely unknown, but it has been accepted that genetic and environmental factors may both be responsible for the disease. Recent studies have revealed that the genes involved in the folate/homocysteine pathway may be risk factors for autistic children. In particular, C677T polymorphism in the MTHFR gene as a possible risk factor for autism is still controversial. We aimed to investigate the possible effect of C677T polymorphism in a Turkish cohort. Methods. Autism patients were diagnosed by child psychiatrists according to DSM-IV and DSM-V criteria. A total of 98 children diagnosed as autistic and 70 age and sex-matched children who are nonautistic were tested for C677T polymorphism. This polymorphism was studied by using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods. Results. MTHFR 677T-allele frequency was found to be higher in autistic children compared with nonautistic children (29% versus 24%), but it was not found statistically significant. Conclusions. We conclude that other MTHFR polymorphisms such as A1298C or other folate/homocysteine pathway genes may be studied to show their possible role in autism.